2016
DOI: 10.5005/jp-journals-10024-1928
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Occlusal Carious Lesion using the SoproLife® Camera: A Systematic Review

Abstract: Aim:The aim of this systematic review was to assess the in vivo scientific evidence regarding the ability of a recently developed light fluorescence device, SoproLife ® (Sopro-Acteon group, La Ciotat, France) in detecting occlusal carious lesions.The PubMed database was searched for in vivo trials that evaluated the validity of the SoproLife ® camera for the detection of occlusal carious lesions. Among the 11 articles originally identified with the keyword "Soprolife," only three articles were included.The thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Further, the device combines a high-magnification intraoral camera and a laser fluorescence device allowing the lesion and its real topography to be seen in a magnified enlarged view [ 13 ], facilitating a better visibility [ 33 , 34 ], as well as a high discrimination, more particularly in anfractuous permanent premolars and molars [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the device combines a high-magnification intraoral camera and a laser fluorescence device allowing the lesion and its real topography to be seen in a magnified enlarged view [ 13 ], facilitating a better visibility [ 33 , 34 ], as well as a high discrimination, more particularly in anfractuous permanent premolars and molars [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…With SoproLife ® , clinicians may visualize and record the lesion, obtain information about the success of long-term protective applications and increase patient motivation by enabling re-evaluation of treatment. Thus, SoproLife ® may support the patient-practitioner communication; and since it is free of ionizing radiation, it could be useful in the carious lesion detection in children and pregnant women [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jablonski-Momeni et al compared near-infrared imaging system (VistaCam iX Proxi) and conventional digital radiographs for the diagnosis of proximal enamel lesions and found that there was moderate agreement between the methods and found no significant difference 18. A recent systematic review on LIF with Soprolife IOC has concluded that there was no clear evidence on the detection of occlusal caries lesions and recommended future studies 19Figure 2Scores of SOPROLIFE in blue fluorescence mode to detect caries.…”
Section: Applications Of Iocmentioning
confidence: 99%
“…A clinical study reported that, when using ICDAS as a reference standard, the performance of the Soprolife in terms of sensitivity and specificity for occlusal caries detection (43%) was less than that of the DIAGNOdent (62%) [71]. In a recent systematic review of the detection of occlusal caries, reported values for sensitivity for the Soporlife ranged between 43% and 95%, and for specificity between 55 and 100% [72]. Due to a limited number of clinical studies, further work is needed to confirm the validity of the SoproLife® intra-oral camera for detecting occlusal carious lesions.…”
Section: Nm Blue Light For Fluorescence Diagnosismentioning
confidence: 99%